Ankylosing Spondylitis Causing Obstructive Lung Disease and Tricuspid Insufficiency: A Case Report - Amisha; Paras Malik; Monika Pathania; Vyas Kumar Rathaur (Journal of Clinical and Diagnostic Research, 2019)
Ankylosing Spondylitis (AS) is a chronic progressive inflammatory spondyloarthropathy typically involving the axial skeleton, especially the sacroiliac joints and spine. Genetic predisposition in AS leads to its common association with certain extra-articular diseases-anterior uveitis (25-30%), psoriasis (10%) and inflammatory bowel diseases (50%). Cardiorespiratory involvement in AS is rare and is usually present in long standing disease as restrictive lung disease, conduction abnormalities or aortic insufficiency. Here, we present a case of unusual AS in a 32-year-old non-smoker male with a major involvement of peripheral joints along with spine and chronic obstructive lung disease with apical fibro-bullous cavity and right sided heart failure over a short duration of disease course. His condition was acutely stabilised with diuretics, anti-hypertensive drugs, anti-pyretics, antibiotics and oxygen inhalation followed by maintenance on Non-steroidal anti-inflammatory agents. Hence, in a patient of AS, a strong index of suspicion should be there for both usual and unusual extra-articular manifestations and a complete work-up would help in early diagnosis and treatment.